1937
DOI: 10.1103/physrev.52.1198
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Cosmic-Ray Particles

Abstract: Bloch and Gentile, " the explanation is probably that the arrangement of atoms in the hexagonal gratings does not deviate too greatly from cubic form. VA'th strict cubic symmetry, the expression (53) would vanish, and with hexagonal the various members of (53) may nearly cancel, so that Q~is considerably smaller than XC in magnitude. There is no corresponding cancellation in the fourthorder coefticient, which one should thus expect to be of about the same order 10' ergs/cm' as the cubic anisotropy coeKcient E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

1938
1938
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 6 publications
1
13
0
2
Order By: Relevance
“…Such particles were believed to be neither the proton nor the electron (positron), presumably having a mass between that of the proton and the electron. In the same year, similar findings were reported by other groups [9,10,11]. Among them, two groups succeeded in determining the mass of such intermediate particles.…”
Section: Discovery Of the "Mesotron"supporting
confidence: 83%
See 1 more Smart Citation
“…Such particles were believed to be neither the proton nor the electron (positron), presumably having a mass between that of the proton and the electron. In the same year, similar findings were reported by other groups [9,10,11]. Among them, two groups succeeded in determining the mass of such intermediate particles.…”
Section: Discovery Of the "Mesotron"supporting
confidence: 83%
“…Thus, it is fair to say that the two experiments [10,11] were nearly of the same quality and significance. Nevertheless, the experiment of Nishina's group has hardly been recognized in the world.…”
Section: Discovery Of the "Mesotron"mentioning
confidence: 95%
“…They concluded that, given its absorption characteristics, the component could consist neither of protons or electrons and that there must be a charged particle of intermediate mass, which they called the 'heavy electron'. Independent observations by Street &Stevenson (1937) andNishina et al (1937) led to the same conclusion. A summary of the observations put the mass between 100 and 400 m e , with a most probable figure of 200 m e .…”
Section: T M mentioning
confidence: 55%
“…In 1937 three groups, S. H. Neddermeyer and C. D. Anderson [13]; Nishina, M. Takeuchi and T. Ichimiya [14,15]; J. C. Street and E. C. Stevenson [16], discovered a new particle with mass consistent with that of Yukawa's particle in the cosmic ray by cloud-chamber experiments. (Fig.3) to Yukawa at Osaka Imperial University for an informal discussion meeting on mesons among theoretical and cosmic-ray physicists [17].…”
Section: The Cosmic-ray Meson (Muon) Was Discovered By Three Groups Imentioning
confidence: 99%